2004
DOI: 10.1063/1.1713034
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated emission and time-resolved photoluminescence in rf-sputtered ZnO thin films

Abstract: Stimulated emission ͑SE͒ was measured from ZnO thin films grown on c-plane sapphire by rf sputtering. Free exciton transitions were clearly observed at 10 K in the photoluminescence ͑PL͒, transmission, and reflection spectra of the sample annealed at 950°C. SE resulting from both exciton-exciton scattering and electron hole plasma formation was observed in the annealed samples at moderate excitation energy densities. The SE threshold energy density decreased with increasing annealing temperature up to ϳ950°C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 18 publications
8
49
0
Order By: Relevance
“…From these data, it is seen that the optimum annealing temperature for ZnO/a-Al 2 O 3 samples is 950°C, at which temperature the mobility has the highest value, 64.4 cm 2 /V Á sec. These results are consistent with the results reported by Ö zgü r et al previously, 8 who found that samples annealed at 950°C had the highest near band edge photoluminescence emission intensity and smallest full-width at half-maximum. Therefore, it was concluded that 950°C is the optimum temperature for ZnO/a-Al 2 O 3 grown by RF sputtering, which through the current study turned out to be the optimum annealing temperature for transport properties as well.…”
Section: Zno/a-al 2 O 3 Samplessupporting
confidence: 96%
See 1 more Smart Citation
“…From these data, it is seen that the optimum annealing temperature for ZnO/a-Al 2 O 3 samples is 950°C, at which temperature the mobility has the highest value, 64.4 cm 2 /V Á sec. These results are consistent with the results reported by Ö zgü r et al previously, 8 who found that samples annealed at 950°C had the highest near band edge photoluminescence emission intensity and smallest full-width at half-maximum. Therefore, it was concluded that 950°C is the optimum temperature for ZnO/a-Al 2 O 3 grown by RF sputtering, which through the current study turned out to be the optimum annealing temperature for transport properties as well.…”
Section: Zno/a-al 2 O 3 Samplessupporting
confidence: 96%
“…The electrical properties were then studied as a function of annealing temperature. Previously, Ö zgür et al 8 studied the dependence of optical properties of RF-sputtered ZnO films and their dependence on annealing temperature with the conclusion that such a treatment led to significant improvement of crystal and optical properties of the ZnO films. However, there were only a few reports on the electrical properties of the ZnO films grown by RF sputtering, 9,10 which constitutes the main topic of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…At the lowest excitation, the emission of exciton-exciton scattering (so-called P -line at ≈ 3.26 eV) was observed. The further increase of excitation energy density revealed EHP emission at ≈ 3.15 eV [9]. We attributed the broadening of the EHP band and shift of the PL spectra maximum to lower energy ("red" shift) with increase of excitation energy density (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The NBE PL band broadening under high excitation (see Fig. 2a) can be explained by accumulation of higher densities of carriers and strong saturation of optical gain [9] in this sample, as well. Let us note that the threshold of SE at 3.15 eV in the MBE-grown layers is around 0.2 mJ/cm 2 which is lower in comparison with Ga-doped ZnO due to lower concentration of intrinsic defects in MBE-grown ZnO layers.…”
Section: Resultsmentioning
confidence: 99%
“…After heating, the substrates were removed from the solution and were washed with distilled water (H 2 O) to remove unwanted residues. The samples were air-dried and then annealed at 500°C for 20 min in ambient air to ensure complete ZnAc decomposition and to obtain samples with better crystallinity [19][20][21].…”
Section: Methodsmentioning
confidence: 99%